2023
DOI: 10.1002/nop2.1670
|View full text |Cite
|
Sign up to set email alerts
|

Intention to leave the profession and related factors in nurses: A cross‐sectional study in Kermanshah, Iran

Abstract: Aim: To investigate the intention to leave the profession and its related factors among nurses in Kermanshah, western Iran.Design: Cross-sectional study.Methods: A total of 377 nurses were enrolled in a stratified random sampling method.Data were collected by the Anticipated Turnover Scale and a sociodemographic information form. and analysed by descriptive and inferential statistics (logistic regression analysis). Results:The results showed that 49.6% (n = 187) of nurses tended to leave the profession and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, the results of the current study, where the p-value was greater than 0.05 (significant level), indicate no significant relationship exists among gender, age, working hospital, and intention to leave. This is consistent with a study conducted in Iran by Maleki et al [22]; the research also revealed no statistically significant correlation among age, gender, and intention to leave.…”
Section: Resiliencesupporting
confidence: 92%
See 2 more Smart Citations
“…However, the results of the current study, where the p-value was greater than 0.05 (significant level), indicate no significant relationship exists among gender, age, working hospital, and intention to leave. This is consistent with a study conducted in Iran by Maleki et al [22]; the research also revealed no statistically significant correlation among age, gender, and intention to leave.…”
Section: Resiliencesupporting
confidence: 92%
“…Regarding the study’s results, Hoseini et al [ 23 ] noted that nurses’ intentions to quit and their shift work were significantly correlated, with morning-shift workers having lower intentions to leave. This contrasts with Maleki et al [ 22 ], who discovered no connection between the type of shift and nurses who intended to quit. Moreover, work units could influence turnover intentions ( p -value = 0.005, F = 2.949).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Since the 1980s, numerous scholars have studied nurse turnover and retention. Large percentages of nurses around the world have reported their intention to leave: Ethiopia, 65%; Saudi Arabia, 62%; Jordan, 61%; the United States, 36% ( Li et al., 2021 ); and Iran, 50% ( Maleki et al., 2023 ). However, there is no standardized way to measure nurses’ intention to stay.…”
Section: Introductionmentioning
confidence: 99%
“…When nurses intend, it can negatively affect the nurse, the patient, and the healthcare facilities' overall performance, stability, and productivity. High nurse turnover rates can increase the workload and stress on remaining nurses, leading to staff fatigue (2,3). Moreover, Increased intention to leave may lead to an increase in the number of new nurses entering the profession, who may need more experience and skills to provide high-quality patient care.…”
Section: Introductionmentioning
confidence: 99%